My home is my castle: The benefits of working from home during a pandemic crisis. Evidence from Germany - Jean-Victor Alipour; Harald Fadinger; Jan Schymik (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper studies the relation between work and public health during the COVID-19 pandemic in Germany. Combining administrative data on SARS-CoV-2 infections and short-time work registrations, firm- and worker-level surveys and cell phone tracking data on mobility patterns, we find that working from home (WFH) is very effective in economic and public health terms. WFH effectively shields workers from short-term work, firms from COVID-19 distress and substantially reduces infection risks. Counties whose occupation structure allows for a larger fraction of work to be done from home experienced (i) much fewer short-time work registrations and (ii) less SARSCoV-2 cases. Health benefits of WFH appeared mostly in the early stage of the pandemic and became smaller once tight confinement rules were implemented. Before confinement, mobility levels were lower in counties with more WFH jobs and counties experienced a convergence in traffic levels once confinement was in place.
Keywords: J22; H12; I18; J68; R12; R23; 330; COVID-19; SARS-CoV-2; working from home; labor supply shock; infections; mitigation; BIBB-BAuA